On the origin of the slow M-T chlorophyll a fluorescence decline in cyanobacteria: interplay of short-term light-responses - Bernát, Gábor; Steinbach, Gábor; Kaňa, Radek; Govindjee; Misra, Amarendra N; Prašil, Ondřej (Photosynthesis research, 2018)
The slow kinetic phases of the chlorophyll a fluorescence transient (induction) are valuable tools in studying dynamic regulation of light harvesting, light energy distribution between photosystems, and heat dissipation in photosynthetic organisms. However, the origin of these phases are not yet fully understood. This is especially true in the case of prokaryotic oxygenic photoautotrophs, the cyanobacteria. To understand the origin of the slowest (tens of minutes) kinetic phase, the M-T fluorescence decline, in the context of light acclimation of these globally important microorganisms, we have compared spectrally resolved fluorescence induction data from the wild type Synechocystis sp. PCC 6803 cells, using orange (λ = 593 nm) actinic light, with those of mutants, ΔapcD and ΔOCP, that are unable to perform either state transition or fluorescence quenching by orange carotenoid protein (OCP), respectively. Our results suggest a multiple origin of the M-T decline and reveal a complex interplay of various known regulatory processes in maintaining the redox homeostasis of a cyanobacterial cell. In addition, they lead us to suggest that a new type of regulatory process, operating on the timescale of minutes to hours, is involved in dissipating excess light energy in cyanobacteria.
Keywords: Potassium Cyanide; chlorofyl; fluorescenční spektrometrie; Phycobilisomes; Light; Fluorescence; Luminescent Measurements; světlo; fykobilizomy; diuron; fluorescence; kyanid draselný; Bacterial Proteins; Spectrometry, Fluorescence; Interplay of regulatory processes; Chlorophyll A; Diuron; Temperature; The M–T phase; Photoprotection; chlorofyl a; Chlorophyll; Synechocystis; luminiscenční měření; Kautsky effect; bakteriální proteiny; Fluorescence quenching; teplota